Utilitarian and Hedonic Shopping Motives and Attitude towards Online Shopping of Generation Z in Indonesia - Dewi, Ike Janita; Mahemba, Umbu Saga Ana Kaka (Yayasan Ilomata, 2024)
The purpose of this study was to analyze the effect of hedonic and utilitarian shopping motives on generation Z's online repurchase intention. The study also aims at examining the interaction between consumers’ internal factor (that is, shopping motives) and external stimuli (i.e, product type) on online repurchase intention. This research uses a quantitative approach, namely explanatory research. The research was conducted on 143 respondents of generation Z in Indonesia. The data analysis technique used in this study is multiple regression with mediating variables and independent sample t-test. The results showed that: 1) Hedonic and utilitarian shopping motives positively affect online repurchase intention of generation Z, 2) Attitudes towards online shopping partially mediated the influenceof utlilitarian and hedonic shopping motives on online repurchase intention of generation Z, 3) Hedonic shopping motives’ influence on online repurchase intention of generation Z is higher than that of utilitarian motives if the product category is a hedonic product, and 4) Utilitarian shopping motives’ influence on online repurchase intention of generation Z is higher than that of hedonic motives if the product category is a utilitarian. The research provides important implications that consumers (especially Generation Z) have hedonic and utilitarian online shopping motives. Therefore, managers need to provide online shopping experience which can evoke both both hedonic and utilitarian shopping motives.